The first desert dust event detected by Cimel photometer in Badajoz station (Spain) - Obregón, Maria Angeles (2015)
This work focuses on the study of the first Saharan desert dust episode detected by the Cimel photometer in Badajoz station (Spain). This station works operatively since June 2012 as part of AERONET (AErosol RObotic NETwork) and RIMA (Red Ibérica de Medida fotométrica de Aerosoles) monitoring networks, and follows their calibration and measuring protocols. Within the short period of measurements, several dust events have been detected. A particularly intense dust outbreak occurred between 8 and 12 August 2012, and was measured at our station. The transport of dust from the Sahara region towards the Iberian Peninsula is one regular phenomenon that notably influences the radiation balance as well as the atmospheric visibility at those sites overspread by these aerosols. This Saharan dust event has been analyzed in terms of the measurements of several optical and microphysical aerosol properties, such as aerosol optical depth, Ångström exponent α, single scattering albedo and size distributions, and the air mass back-trajectories computed by means of the Hybrid Single Particle Lagrangian Integrated Trajectory model (HYSPLIT4). The measurements show a significant increase in the atmospheric turbidity caused by the inflow of coarse particles, with daily averages of aerosol optical depth at 500nm of about 0.5, Ångström exponent α of about 0.2, and single scattering albedo values over 0.9. These values and their range of variation are typical for desert dust intrusions.